Kemampuan Mengembangkan Kalimat Utama dalam Paragraf pada Siswa Kelas X SMA Muhamadiyah 2 Bandar Lampung Tahun Pelajaran 2022/2023 - Alfiawati, Riska; Rohana, Rohana (Lentera: Jurnal Ilmiah Kependidikan, 2023)
Efforts to achieve maximum Indonesian learning outcomes in the learning process must be in accordance with adequate situations and conditions, as well as appropriate learning strategies so that they can have a positive effect on the effectiveness of the learning process in achieving learning objectives, such as by using the application of teaching variations. This study uses a quantitative descriptive method. The tools and techniques for collecting data are assignment test techniques, while for analyzing the data used descriptive quantitative. Based on the results of data analysis, it was found that students who reached the excellent category were 6 people or 24%, those who reached the good category were 5 people or 20%, those who reached the moderate category were 11 people or 44%, and students who reached the less category were 3 people or 12%. The average value of the ability to develop main sentences into student paragraphs is 72.4%.